The characteristics of purpose-built office: occupants’ perception - Mohd Safian, Edie Ezwan (e-International Publishing House, Ltd., 2018)
Report from Asia Pacific Colliers had suggested that continued proactive marketing efforts and tenancy offerings could maintain the local office market performance. Therefore, the characteristics of PBO are significant factors that need to be studied. The aim of this paper is to examine the occupiers’ perceptions and needs as well as the importance of the characteristics that applied in PBO. Hence, this paper identified the issues that could provide ideas to the property market participants in improving PBO’s market and building performance via investigating the perception of occupants in order to determine the factors that affect office market property performance.